Shīʿa Literature in Indonesia: A Historical Account - Hidayatullah, Muh. Safrani; Karimullah, Suud Sarim; Septiani, Rina (IAIN Ponorogo, 2025)
This study aims to trace the development and characteristics of various shīʿa literature in Indonesia from a historical perspective. This study uses library research, which allows for integrative and connective tracing of various literature as the primary source of data, which is analyzed through a descriptive approach considering historical dimensions. The findings reveal that the existence and development of shīʿa literature in Indonesia are not merely a historical reflection of the diversity of Islamic sects, but also a manifestation of intellectual dynamics that continue to transform within local and global contexts. The shīʿa tradition, which the majority has long overshadowed, has played a vital role in shaping Islamic discourse in Indonesia through institutional contributions, such as educational foundations, publishing, and academic networks spread across various Islamic universities. Amidst stereotypes and narrative challenges, this development reflects an epistemological openness among Indonesian Muslims who are slowly beginning to recognize the importance of inter-sectarian interaction in building a more comprehensive Islamic intellectual horizon. However, limited access to shīʿa literary archives, the dominance of publishing biases, and the lack of representation in mainstream academic discourse serve as reminders that the process of scholarly integration still requires sustainable and inclusive strategies.